Widening potential window of flexible solid-state supercapacitor through asymmetric configured iron oxide and poly(3, 4-ethylenedioxythiophene) polystyrene sulfonate coated multi-walled carbon nanotubes assembly. (October 2020) - Karade, Swapnil S.; Raut, Shrikant S.; Gajare, Hemant B.; Nikam, Pratibha R.; Sharma, Rajendrakumar; Sankapal, Babasaheb R.
Highlights: Cost-effective and facile synthesis methods. Novel Fe2 O3 //MWCNTs/PEDOT:PSS asymmetric cell. Widen potential window of 1.8 V. High specific energy and specific power. Abstract: Current smart energy storage technology needs flexible, compact and even wearable devices with a wide potential window. As a requisite, a novel flexible all-solid-state asymmetric capacitor (ASC) based on worm-like nanostructured iron oxide (γ-Fe2 O3 ) as negative electrode have been selected properly in combination with poly(3, 4-ethylenedioxythiophene): polystyrene sulfonate (MWCNTs/PEDOT:PSS) coated multi-walled carbon nanotubes as a positive electrode to achieve wide potential window of 1.8 V and the use of facile, low cost and binder free approach for the synthesis are the novelties of the present report. These two electrodes have been sandwiched by CMC-Na2 SO4 gel electrolyte. Chemical bath deposition method has been used to deposit γ-Fe2 O3 thin film while 'dip and dry' coating technique to deposit MWCNTs/PEDOT:PSS composite thin film. Strikingly, the resulting γ-Fe2 O3 //MWCNTs/PEDOT:PSS asymmetric cell yields a wide voltage window of 1.8 V with a high specific capacitance of 65 F g −1 at 2.4 A g −1 current density with good specific energy and specific power. Furthermore, ASC device was capable of 80% retention at 5000 cycles through charge-discharge studies at current density of 2.5 A g −1 along with the flexibility test by bending the device to 170° delivering only 15% capacity loss as per initial one. Graphical abstract: Flexible solid-state asymmetric capacitor cell based on γ-Fe2 O3 as a negative electrode and MWCNTs/PEDOT:PSS as a positive electrode prepared and practically demonstrated. Image, graphical abstract